Analisis Kondisi dan Efektivitas Penggunaan Fasilitas Jembatan Penyeberangan Orang (JPO) di Kota Jayapura - Deannaz Ultima Avissaputri; Monita Yessy Beatrick Wambrauw; Marsal Arung Lamba (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The high pedestrian activity and traffic flow in the education area on Jalan Raya Abepura-Sentani Jayapura City led to the provision of Pedestrian Bridges (JPO) in two locations, namely in front of the Cenderawasih University Auditorium (JPO-1) and in front of SMP YPPK Santu Paulus (JPO-2). This research was conducted to determine the suitability of the physical geometric standards of the pedestrian bridge and its level of effectiveness, as well as factors that affect pedestrian satisfaction in using the two Pedestrian Bridge (JPO) facilities. Geometric analysis was carried out using the standard of Pedestrian Bridge Planning Procedures for Urban Pedestrians (1995) and Technical Planning of Pedestrian Facilities (2023), calculation of the level of effectiveness using the volume of crossings, and analysis of service satisfaction using the Importance Performance Analysis (IPA) method. The results found that the condition of JPO-2 is better and meets the standards because it uses a slope that can be used by people with disabilities, while the slope on the steps of JPO-1 is too steep (40°) and narrow with a width of 1.4 meters, so the effectiveness level of JPO-2 is higher (67%) than JPO-1 (52%). Factors affecting user satisfaction are aspects of comfort, safety, and security. The main obstacles in using the pedestrian bridge are dirty conditions, no lighting, the presence of people under the influence of alcohol or extortionists, and damage to the Pedestrian Bridge (JPO) facilities.